Cross-cultural adaptation and validation of the Spanish version of the American Academy of Orthopaedic Surgeons-Foot and Ankle Module (AAOS-FAMsp). - González-Sánchez, Manuel; Velasco-Ramos, Esther; Ruiz-Muñoz, María; Cuesta-Vargas, Antonio (BMC, 2016)
Background: The current study performed a cross-cultural adaptation to Spanish and examined the internal and external validation of the AAOS-FAM questionnaire. Methods: A direct translation (English to Spanish) and a reverse translation (Spanish to English) were performed by two independent professional native translators. Cronbach's α coefficients were calculated to analyse the internal consistency of the measure. The factor structure and construct validity were analysed after extraction by maximum likelihood (EML); extraction was necessary if the following three requirements were met: accounting for ≥10 % of variance, Eigenvalue >1.0 and a scree plot inflexion point. The standard error of measurement and minimal detectable change 90 (MDC90) were calculated. Criterion validity was calculated by analysing the correlation between the American Academy of Orthopaedic Surgeons-Foot and Ankle Module (Spanish version) (AAOS-FAMsp) and Spanish versions of the questionnaires FFI and FHSQ. Results: Regarding internal consistency, Cronbach's α was 0.877, and in the test-retest analysis, the ICC ranged between 0.899 and 0.942. Error measures were calculated by MDC90 and SEM, which showed values of 3.444 and 1.476 %, respectively. The analysis demonstrated a goodness of fit chi-squared value of 803.166 (p < 0.001). For criterion validity, the correlation value with FFIsp was r = 0.837 (p < 0.01), while the FHSQsp correlation values with different scales ranged from r = 0.206 (p < 0.01) (physical activity) to r = 0.665 (p < 0.01) (pain). Conclusions: The results indicate that AAOS-FAMsp has satisfactory psychometric properties, facilitating the inclusion of Spanish-speaking individuals into both research and clinical practice.
Keywords: Pies - Lesiones y heridas; Tobillos - Lesiones y heridas; Pacientes - Rehabilitación; Assessment; Foot; Patient reported outcome measures; Spanish version; Validation